Germline Genetics of the p53 Pathway Affect Longevity in a Gender Specific Manner - Groß, Sebastian; Immel, Uta-Dorothee; Klintschar, Michael; Bartel, Frank (Current Aging Science, 2014)
Aging is thought to occur through the accumulation of molecular and cellular damage. A key regulator of the cell’s stress response is p53. In mice, the activity of p53 associates with lifespan. We were therefore interested whether SNPs in members of the p53-pathway are associated with longevity in humans. We genotyped the following SNPs: p53 – rs1042522 (Arg72Pro), MDM2 – rs2279744 (SNP309), MDM4 – rs4245739 (SNP34091), rs1563828 (SNP31826), PPP2R2B (rs319217) in 155 long-lived individuals (LLIs) who died at the age of 91 and over and in 171 ethnicallymatched control subjects. Kaplan-Meier survival curves and log-Rank-test were used to determine the mean and median survival times. In female LLIs, the Pro-allele of rs1042522 (Arg72Pro) and the G-allele of rs2279744 (SNP309) were significantly associated with an increased survival time (P =0.026, P <0.001, respectively, log-Rank-test). In contrast, there was no difference regarding the survival time in male LLIs (rs1042522: P=0.58, rs2279744: P =0.503, log-Rank-test). There was no difference regarding the average age of death for the genotypes of the respective SNPs in the MDM4 gene (rs1563828: P =0.99; rs4245739: P =0.179, respectively). Here we show for the first time that the G-allele of rs2279744 (SNP309) is associated with increased lifespan. Importantly, this effect is gender-specific. Our data support the hypothesis that genetic variants that are associated with lower activity of p53 – and therefore increased tumor risk – are associated with prolonged lifespan in a gender-specific manner.
Keywords: MDM2